2020
DOI: 10.1136/emermed-2019-208836
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the National Emergency Department Overcrowding Score (NEDOCS) in a UK non-specialist emergency department

Abstract: IntroductionEmergency department (ED) crowding has significant adverse consequences, however, there is no widely accepted tool to measure it. This study validated the National Emergency Department Overcrowding score (NEDOCS) (range 0–200 points), which uses routinely collected ED data.MethodsThis prospective single-centre study sampled data during four periods of 2018. The outcome against which NEDOCS performance was assessed was a composite of clinician opinion of crowding (physician and nurse in charge). Are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Whether the measure works well outside the USA. 17,18 A study conducted by Raj et al in Australia concluded that the NEDOCS tool needed to be more valid in their setting, owing to inconsistencies in the reflection of the staff's sense of 'overcrowding'. However, they opined that NEDOCS is a significant instrument which has the potential to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the measure works well outside the USA. 17,18 A study conducted by Raj et al in Australia concluded that the NEDOCS tool needed to be more valid in their setting, owing to inconsistencies in the reflection of the staff's sense of 'overcrowding'. However, they opined that NEDOCS is a significant instrument which has the potential to be improved.…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 17 , 18 A similar methodology has been used for the National Emergency Department Overcrowding Study with comparable, replicable results. 19 , 20 , 21 Mixed model linear regression, using the restricted maximum likelihood function, was used to test the effects of TTB on OR with additional fixed effects and hospital type, hospital size, staff‐to‐patient ratio, and ED as random effect variables. The effects of OR and TTB on assessed workload were investigated similarly.…”
Section: Methodsmentioning
confidence: 99%
“…There is no literature regarding which predictor variables or techniques should be used, nor is there information about whether a single site-derived model would apply to multiple emergency departments for systemwide implementation. Cooney et al 5,6 considered whether the National Emergency Department Overcrowding Score (NEDOCS) 7,8 may be a useful predictor variable or model, with the association describing the relationship between access block and ambulance ramping. Others have explored centralized ambulance patient distribution optimization.…”
Section: Importancementioning
confidence: 99%